Penyakit Asbes Akibat Kerja di Indonesia: Himbauan untuk Segera Melakukan Tindakan dan Kesadaran - Dwi Lestari, Ade; Hairunisa, Nany; Mohamad Ridwan, Alvin (Fakultas Kedokteran Universitas Trisakti, 2023)
Despite many countries have either reduced or banned asbestos use, Indonesia has yet to ban the use of asbestos. Asbestos exposure poses significant health risks, particularly respiratory diseases such asbestos-related lung cancer, mesothelioma, and asbestosis known as an asbestos-related disease. According to the World Health Organization (WHO), asbestos is a major global health concern with millions of people exposed to its hazards and resulting in a significant number of deaths each year. We conducted a literature review study on the topic of asbestos-related diseases in Indonesia. Based on our findings, due to the large amount of asbestos being handled, it is expected that there should be hundreds to a thousand cases of asbestos-related disorders in Indonesia each year. Unfortunetely it is uncommon to find and diagnose cases of asbestos-related diseases in Indonesia. The lack of awareness, inadequate diagnosis, and underreporting of asbestos-related diseases contribute to the challenges faced in Indonesia. The study emphasizes the need for a comprehensive ban on asbestos, safer alternative materials, standardized medical surveillance for exposed workers, increased awareness and cooperation among stakeholders to eliminate asbestos-related diseases in Indonesia.